Enhancing Creativity in the School Environment. A Narrative Examination - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tsagri, Angeliki; Tseremegklis, Chrysostomos; Asimakopoulou, Sofia (Technium Education and Humanities, 2023)
The cultivation of creativity within the educational environment is of utmost importance in the context of our contemporary, rapidly changing society. This research paper explores the importance, difficulties, and approaches to promoting creativity in educational settings. Creativity plays a crucial role in the growth and advancement of individuals, encompassing both educational and developmental domains. The absence of creativity has a pervasive influence on the entire school community, resulting in detrimental consequences, whereas its cultivation is advocated to improve the educational experience. This study aims to examine the significance of creativity within the educational setting. The present study constitutes a comprehensive examination of the existing body of literature from 1999 to 2023. Following a rigorous and comprehensive assessment of the articles, eleven (11) articles were selected for inclusion in the study. This study examines multiple research papers that investigate creativity in the educational setting. Specifically, it focuses on the perspectives of both students and teachers regarding the manifestation of creativity. Additionally, it explores the relationship between teachers' expertise and their ability to facilitate creative activities and the interplay between children's creative abilities and their academic performance. In summary, various factors influence the development of creativity and associated skills in individuals, with a notable emphasis on the school community. Nevertheless, educational institutions require assistance in transitioning from traditional approaches and effectively evaluating the concept of creativity. Even with these challenges, the imperative of prioritizing creativity in education is apparent, considering its pivotal role in fostering comprehensive student growth and equipping learners for forthcoming obstacles. The paper concludes by advocating for schools to adopt a proactive role in fostering creativity, thereby equipping students with the necessary skills to navigate the intricate challenges of the 21st century effectively.